Factors Influencing the Choice of Entry Mode Strategies for Internationalization: A Study on the Readymade Garments (RMG) Industry of Bangladesh - Russel, Aminul Haque; Robidas, Lakkhan Chandra; Nipa, Shakila Jahan; Akter, Fahmida (The journal of contemporary issues in business and government, 2021)
The purpose of this research is to identify the factors influencing the choice of entry mode strategies for internationalization. In order to meet the research objectives the quantitative method, in the form of survey, was adopted in this research. A self- administrative structured survey questionnaire consisting with a set of close-ended questions was developed to collect statistics data which were later analyzed using quantitative data analysis technique to make a conclusion of the research. The study identified that time to market, resources and capabilities, flexibility, risk, return on investment, long-term goal, international relation and experience, law and regulations, uncertainty to access demand, trade barriers, Market size & growth and competition are the influential factors of foreign market entry mode choice of Bangladesh RMG manufactures.